Prevalence of overweight and obesity in children and adolescents with intellectual disabilities in China. Issue 7 (14th April 2021) - Yuan, Y. Q.; Liu, Y.; Wang, M. J.; Hou, X.; Zhang, S. H.; Wang, X. L.; Han, Y. N.; Sang, P.; Bian, Y.; Roswal, G.
Abstract: Background: Overweight and obesity in children and adolescents has become a worldwide epidemic. There are several studies that have concentrated on the prevalence rate of children and adolescents with intellectual disabilities (ID), whereas data on such a population on the mainland of China remain unclear. The purpose of this study was to investigate the prevalence rate of overweight and obesity among school‐aged children and adolescents with ID on China's mainland. Methods: This study employed a cross‐sectional design to examine the body weight status of 1873 children and adolescents (ages 6–18 years old) with ID in 35 special education schools. Body mass index was calculated, and the concepts of overweight and obesity were defined according to the standard of the Working Group for Obesity in China. Results: Data indicated that 18.2% (95% CI: 16.5%–20.0%) of children and adolescents with ID were overweight and 14.4% (95% CI: 12.8%–16.0%) were obese. Boys with ID were more likely to be overweight than girls with ID (OR = 1.48[95% CI: 1.13–1.94], P  < 0.05). Children and adolescents with Down syndrome or autism spectrum disorder had a trend to be classified as overweight (OR = 1.76[95% CI: 1.22–2.54], P  < 0.05; OR = 1.57[95% CI: 1.17–2.09], P  < 0.05, respectively) or obesity (OR = 1.82[95% CI: 1.23–2.69], P  < 0.05; OR = 1.40 [95% CI: 1.02–1.93], P  < 0.05, respectively) compared with those with ID without these conditions. Moreover, children and teenagers with ID living in urban areas had a predisposition to be overweight (OR = 2.16[95% CI: 1.14–4.09], P  < 0.05) or obese (OR = 3.25[95% CI: 1.41–7.50], P  < 0.05) relative to those who lived in rural areas. Conclusion: Results indicated that in China, the prevalence rate of overweight and obesity among school‐aged children and adolescents with ID was remarkably high. Therefore, future research should make every effort to focus on reducing and preventing overweight and obesity of this population in China.